2016
DOI: 10.1007/s12640-016-9646-0
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity in the Post-HAART Era: Caution for the Antiretroviral Therapeutics

Abstract: Despite the advent of highly active antiretroviral therapy (HAART), HIV-associated neurological disorders (HAND) remain a major challenge in human immunodeficiency virus (HIV) treatment. The early implementation of HAART in the infected individuals helps suppress the viral replication in the plasma and other compartments. Several studies also report the beneficial effect of drugs that successfully penetrate central nervous system (CNS). However, recent data in both clinical setup and in in vitro studies indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 177 publications
0
61
0
1
Order By: Relevance
“…In addition, two drugs, ritonavir (RTV) and cobicistat (COBI) are used as pharmacokinetic enhancers [124] (reviewed in [125,126]). The Department of Health and Human Services (HHS) Panel on Antiretroviral Guidelines for Adults and Adolescents (a working group of the office of AIDS research) [124] keep updating the combination regimens, based on more than 25 antiretroviral drugs approved by the Food and Drug Administration (FDA) in order to guide to the right and best treatment for HIV + individuals.…”
Section: Neurotoxicity Of Antiretroviral Drugsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, two drugs, ritonavir (RTV) and cobicistat (COBI) are used as pharmacokinetic enhancers [124] (reviewed in [125,126]). The Department of Health and Human Services (HHS) Panel on Antiretroviral Guidelines for Adults and Adolescents (a working group of the office of AIDS research) [124] keep updating the combination regimens, based on more than 25 antiretroviral drugs approved by the Food and Drug Administration (FDA) in order to guide to the right and best treatment for HIV + individuals.…”
Section: Neurotoxicity Of Antiretroviral Drugsmentioning
confidence: 99%
“…However, the occurrence of cognitive impairment milder than HAD persists in HIV patients on cART [9,11,31] and recent studies observed that discontinuation of cART in virologically controlled HIV patients unexpectedly resulted in significant improvement of neurocognitive function [32,33,34,35]. Furthermore, clinical and experimental evidence is accumulating that at least some ARV compounds may themselves have neurotoxic effects [36,37,38,39,40,125,130]. …”
Section: Neurotoxicity Of Antiretroviral Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the use of the integrase inhibitor raltegravir has been associated with neuropsychiatric symptoms (Harris et al , 2008; Teppler et al , 2011). Several of these ARVs have also been shown to lead to CNS abnormalities in rodent models (Shah et al , 2016). Mitochondrial effects have been examined for a number of these ARVs, as discussed below.…”
Section: Discussionmentioning
confidence: 99%